Mrs DESAIN MODEL KETERAMPILAN BERPIDATO INOVATIF - Siregar, Yunarni; Herlina, Herlina; Sintowati Rini Utami (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
Speech skills are an important part of oral communication skills that are very much needed in the world of education, social, and professional. However, in practice, learning speech skills is still often done conventionally and is less engaging, so it is unable to encourage active participation and build students' self-confidence. This study aims to develop an innovative speech skills model design that can improve students' abilities in composing, delivering, and mastering speeches effectively. The approach used is research and development (R&D), with stages of needs analysis, conceptual model design, expert validation, and offering innovative model designs. This model is designed by integrating a communicative approach, project-based learning, and exploring the use of interactive digital media in the form of videos and other presentation support applications. Interviews involved 609 grade XI students from several high schools in Jakarta. The results of the interviews showed that this model is very much needed and feasible to be implemented. These findings are expected to be an alternative innovative design in learning speaking skills, especially speech, especially in the development of multimodal-based learning.